Предмет: Геометрия,
автор: Олег111111
Cпростити вираз (1+cosα)(1-cosα)
Довести тотожність tg²α-sin²α·tg²α=sinα
За відповідь 40 балів
Ответы
Автор ответа:
0
1)(1-cosa)(1+cosa)=1-cos²a=sin²a
2)tg²a-sin²a*tg²a=tg²a(1-sin²a)=sin²a/cos²a * cos²a=sin²a
2)tg²a-sin²a*tg²a=tg²a(1-sin²a)=sin²a/cos²a * cos²a=sin²a
Похожие вопросы
Предмет: Алгебра,
автор: seriknargiz
Предмет: Биология,
автор: 0507mila02
Предмет: Химия,
автор: tomtorchik
Предмет: Математика,
автор: ramses88888888
Предмет: Математика,
автор: natalifridrikh